Utilization of Xpert MTB/RIF molecular test and Thorax Radiography as Tuberculosis Screening at PKU Muhammadiyah Bantul Hospital - Prisila, Elvina; Sukirto, Novi Wijayanti; Umam Kurniawan, Nurcholid; Rahayu, Ana Budi; Yuniasih, Dewi; Wira Oktaviana, Ardyawati; Putri Nurulita, Febrianti; Sholikhah, Amanatus; Awisarita, Wiwara (Ahmad Dahlan Medical Journal, 2024)
Tuberculosis is a disease caused by the bacteria Mycobacterium tuberculosis, and approximately 25% of the global population is afflicted with this bacterium. In 2022,The objective of this study is to assess the effectiveness of the Xpert MTB/RIF Molecular Test and Thorax Radiography as diagnostic tools for tuberculosis at PKU Muhammadiyah Bantul Hospital. The research employed quantitative methodologies with a cross-sectional design. The majority of tuberculosis suspects at PKU Muhammadiyah Bantul Hospital were individuals aged 64 years or older, based on age group. In terms of gender, 498 individuals were male. According to the Xpert MTB/RIF molecular test, 89 individuals tested positive for tuberculosis. In contrast, the number of individuals who tested positive for tuberculosis through thorax photo examination was 184. The findings indicate that the majority of patients suspected of having Tuberculosis were males and were primarily in the age category of above 64 years old. Thorax photo radiography yielded a higher number of confirmed positive tuberculosis findings compared to the Xpert MTB/RIF molecular test, based on the evaluation of individuals suspected of having tuberculosis.